Metode Tafsir Al-Qurtubi terhadap Ayat Hukum Tindak Pidana Pembunuhan - Parhan, Parhan (STAINI Press, 2023)
This study discusses the methodology used in the interpretation of al-Qurţubi by Imam al-Qurţubī. The main objects that are the focus of research in this study are; Al-Qurtubi's method of interpreting Q.S Al-Baqarah 2:178 which is related to the crime of murder. This research is a type of library research (library study). Because this research uses descriptive and qualitative research. The data sources used in this research are books, journals and scientific works related to the research topic. After the data is collected, it is continued with data analysis and drawing conclusions as a result of the research. The data used in this research is primary data, namely the book Tafsir al-Jāmi‘ li Aĥkām al-Qur'an and secondary data which includes works related to tafsir al-Jāmi‘ li Aĥkām al-Qur'an. This research found several findings, among others, (1) Al-Qurţubī provides analysis in terms of language, (2) Al-Qurţubī interprets verses with the interpretation of al-Ma'tsur and al-Ra'yi, (3) this book of tafsir has a pattern fiqhi or law.